Unpacking Polycentric Climate Governance: Tracing the Evolution of Transnational Municipal Networks over Time - Kristine Kern; Peter Eckersley; Elisa Kochskämper; Wolfgang Haupt (Global Environmental Politics, 2024)
All governance systems are polycentric to some extent in that they comprise multiple actors with varying degrees of autonomy. However, there has been limited theorization as to how we might measure polycentricity, even though this could help us unpack networks and understand governance arrangements better. We present three dimensions of governance to conceptualize degrees of polycentricity—governance of networks (internal organization and management at the network level), governance by networks (their impacts at the membership level), and governance with networks (collaboration with other actors at the system level). We then trace the evolution of three transnational municipal networks (the Climate Alliance, Covenant of Mayors, and 100 Resilient Cities/Resilient Cities Network), which are located at different positions along the polycentric–monocentric spectrum. We examine how these networks have become more or less polycentric over time and highlight trade-offs between different dimensions of polycentric governance, most notably governance of and governance by.
Keywords: 300